IMPLEMENTASI MODEL PEMBELAJARAN BLENDED LEARNING TIPE FLIPPED CLASSROOM UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK - Wulandari, Yessi; Halim, Abdul; Nasrullah, Nasrullah; Syukri, Muhammad; Elisa, Elisa (Balai Diklat Keagamaan Bandung, 2023)
The goal of this research was to find out if students were more enthusiastic about learning about mechanical wave material using the flipped-classroom paradigm of blended learning. The methodology of this investigation is quantitative. This study used a quasi-experimental strategy based on a pre- and post-test control group design. This study was carried out at SMA Negeri 1 Bireuen. Students from SMA Negeri 1 Bireuen's IPA class of the 2021–2022 school year made up the study's population. This research employed a